2014
DOI: 10.1155/2014/950754
|View full text |Cite
|
Sign up to set email alerts
|

Histological Comparison of Two Cryopeeling Methods for Photodamaged Skin

Abstract: Background. Cryopeeling is a technique that uses cryotherapy not only on actinic keratoses lesions, but also all over the photodamaged skin. Objectives. To investigate the histological changes induced by two cryopeeling methods (liquid nitrogen (LN) and portable system (PS)). Methods. Sixteen patients (n = 16) with multiple actinic keratoses on the forearms were treated with cryopeeling technique using LN for one forearm and PS for the other, randomly. Skin biopsies were taken before and after the procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…In accordance with our results, histological analysis of photodamaged skin treated with cryopeeling technique showed a tendency for increase in epidermal thickening and decrease of pigment intensity (Deonizio et al, ). It has been suggested that cryopeeling allows the treatment of entire photodamaged area and would improve the appearance of the skin with additional benefit of preventing the appearance of malignant lesions (Deonizio & Mulinari‐Brenner, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with our results, histological analysis of photodamaged skin treated with cryopeeling technique showed a tendency for increase in epidermal thickening and decrease of pigment intensity (Deonizio et al, ). It has been suggested that cryopeeling allows the treatment of entire photodamaged area and would improve the appearance of the skin with additional benefit of preventing the appearance of malignant lesions (Deonizio & Mulinari‐Brenner, ).…”
Section: Discussionsupporting
confidence: 92%
“…It seems that cryopeeling would lead to better improvement of solar lentigines. Previous reports have shown excellent results with cryopeeling in treatment of actinic keratosis and photodamaged skin (Chiarello, ; Deonizio et al, ; Deonizio & Mulinari‐Brenner, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, the longer the source-to-detector separation (SDS) is, the more the deepest-travelling photons can be detected [17]. It is therefore of interest to take advantage of spatial resolution (several SDS) in order to probe photons that travel both within the epidermis (where cancers develop) and down to the upper dermis (as dermis fibers such as collagen and elastin are also impaired during carcinogenesis [18]).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of dermatology, cryotherapy has been used to provide exfoliation for treatment of actinic keratoses and photodamaged skin by a cryo-peeling technique. 5 WBC does not reach the similar tissue temperatures and remains non-ablative. Therefore one would expect to achieve only a mild clinical improvement for related skin disorders.…”
mentioning
confidence: 96%